Principles and practice of stress management - Lehrer, Paul M., ....-; Woolfolk, Robert L., ....- (New York (N.Y.) : Guilford press, 2021)
"The leading clinical reference and text on stress management has now been significantly revised with 60% new material reflecting key developments in the field. Foremost experts review the "whats," "whys," and "how-tos" of progressive relaxation, biofeedback, meditation, hypnosis, cognitive methods, and other therapies. Chapters describe each method's theoretical foundations, evidence base, procedures, applications, and contraindications. Assessment and implementation are illustrated with extensive case examples. The volume examines the effects of stress on both mind and body, from basic science to practical implications for everyday life and health care. Subject areas/key words: managing, reduction, relaxation, mindfulness, meditation, pain, biofeedback, interventions, anxiety disorders, techniques, psychotherapy, hypnosis, cognitive therapy, breathing retraining, treatments, textbooks, clinical health psychology, behavioral medicine, psychosomatic Audience: Clinical and health psychologists, psychiatrists, clinical social workers, counselors, and nurses; advanced students in these fields"--
Includes bibliographical references and index.
Keywords: Stress (Psychology) -- Prevention; Stress (Psychology) -- Prevention; Stress (Psychology) -- Treatment; Stress (Psychology) -- Treatment; Stress management; Stress management